Gb3 Glycosphingolipids with Fluorescent Oligoene Fatty Acids: Synthesis and Phase Behavior in Model Membranes. (20th September 2017) - Patalag, Lukas J.; Sibold, Jeremias; Schütte, Ole M.; Steinem, Claudia; Werz, Daniel B.
Abstract: Glycosphingolipids are involved in a number of physiological and pathophysiological processes, and they serve as receptors for a variety of bacterial toxins and viruses. To investigate their function in lipid membranes, fluorescently labeled glycosphingolipids are highly desirable. Herein, a synthetic route to access Gb3 glycosphingolipids with fluorescently labeled fatty acids, consisting of pentaene and hexaene moieties either at the terminus or in the middle of the acyl chain, has been developed. The fluorescent properties of the Gb3 derivatives were investigated in small unilamellar vesicles composed of a raft‐like mixture. Phase‐separated giant unilamellar vesicles (GUVs) allowed the quantification of the apparent partitioning coefficients of the Gb3 compounds by means of confocal fluorescence laser scanning microscopy. The determined partition coefficients demonstrate that the Gb3 derivatives are preferentially localized in the liquid‐disordered (ld ) phase. To analyze whether the compounds behave like their physiological counterparts, Cy3‐labeled (Cy: cyanine) Shiga toxin B subunits (STxB) were specifically bound to Gb3 ‐doped GUVs. However, the protein was favorably localized in the ld phase, in contrast to results reported for STxB bound to naturally occurring Gb3, which is discussed in terms of the packing density of the lipids in the liquid‐ordered (lo ) phase. Abstract : Get in place ! Fluorescent labels can alter the phase behavior of lipids considerably. The synthetic route to fatty acid‐labeled Gb3 derivatives that partition in the liquid‐disordered phase, even after binding of Shiga toxin B subunits, is described.